A multiplex allele‐specific real‐time polymerase chain reaction assay for HLA‐B*13:01 genotyping in four Chinese populations. (24th August 2016) - Liu, Z.; Chen, G.; Kang, X.; Han, M.; Chen, R.; Chen, C.; Wang, H.
Abstract: Human leukocyte antigen HLA‐B*13:01 is identified currently as a marker of individual susceptibility to drug‐induced hypersensitivity reaction, such as dapsone‐induced hypersensitivity reactions (DIHRs) and trichloroethylene‐induced dermatitis. Therefore, screening for the HLA‐B*13:01 allele can assist clinics in identifying patients at risk of developing DIHRs. By combining the allele‐specific primers with TaqMan probes, we established a single tube, triplex real‐time PCR to detect HLA‐B*13:01 . The reliability of this assay was validated by the comparison of genotyping results with those by sequence‐based typing (SBT). With this assay, the distribution of HLA‐B*13:01 in a total of 350 blood samples from four ethnic groups: Han, Tibetan, Uighur, and Buyei were determined. A 100% concordance was observed between the results with the established real‐time PCR and SBT in 100 samples. The detection limit of this assay was 0.016 ng genomic DNA. The prevalence of HLA‐B*13:01 carriers were 11%, 8%, 1%, and 2% in the Buyei ( n = 100), Northern Han ( n = 100), Tibetan ( n = 100), and Uighur ( n = 50) populations, respectively. The multiplex real‐time PCR assay provided a fast and reliable method for accurate detection of HLA‐B*13:01 allele prior to dapsone administration in clinical practice and onset of the reaction after exposure to trichloroethylene.